The Influence of Work Discipline, Motivation and Compensation on Employee Work Achievement in the Personnel Agency and Human Resource Development Buru district - Kasim Samak; Conchita V. Latupapua; Etty Puji Lestari (Enrichment : Journal of Management, 2022)
This research was conducted with the aim to find out whether Work Discipline, Motivation and compensation have a partial effect on employees performance at the Employment and Human Resources Development Agency of Buru Regency, Maluku Province, the research method used is causal associative analysis method with quantitative techniques. The data used in this study are primary data and secondary data. The population in this study amounted to 54 people who were all ASN at the Employment and Human Resources Development Agency, Buru Regency, Maluku Province. The sampling method used is saturated or census sampling. The results of this study indicates that Work Discipline, Motivation and compensation simultaneously have a positive and significant effect. The regression transformation coefficient X1 or for the discipline variables is 0.243 with a significance number of 0.026, this value is smaller than α = 5% (0.026 <0.05) and the t- count > t- table value is 2.287 > 1.67356. The coefficient value is positive and partially has a significant effect on work performance (Y). The regression transformation coefficient X2 or for the motivational variables is 0.309 with a significance number of 0.006, this value is smaller than α = 5% (0.006 <0.05) and the value of t- count > t- table is 2.857 > 1.67356. The coefficient value positive and partially has a significant effect on work performance (Y). The regression transformation coefficient X3 or for the compensation variables is 0.267 with a significance number of 0.010, this value is smaller than α = 5% (0.010 <0.05) and the value of t- count > t- table is 2.672 > 1.67356. The coefficient value positive and partially significant effect on work performance (Y).